Development of a gas chromatography system coupled to a metal-oxide semiconductor (MOS) sensor, with compensation of the temperature effects on the column for the measurement of ethene - M. Koehne; M. Koehne; C. Schmidt; S. Singh; A. Grasskamp; T. Sauerwald; T. Sauerwald; G. Zeh (Journal of Sensors and Sensor Systems, 2023)
A possible way to reduce the size and complexity of common gas chromatography (GC) systems is the economization of the column temperature regulation system. To this end, a temperature compensation method was developed and validated on a benchtop GC-PDD (pulsed discharge detector) with ethene. An in-house-developed algorithm correlates the retention index of a test gas to the retention index of a previously selected reference gas. To investigate further methods of cost reduction, commercial gas sensors were tested as cheap, sensitive, and versatile detectors. Therefore, CO2 was chosen as a naturally occurring reference gas, while ethene was chosen as a maturity marker for climacteric fruits and hence as a test gas. A demonstrator, consisting of a simple syringe injection system, a PLOT (porous layer open tubular) column boxed in a polystyrene-foam housing, a commercial MOS (metal-oxide semiconductor) sensor for the test gas, and a CO2-specific IR (infrared) sensor, was used to set up a simple GC system and to apply this method on test measurements. Sorption parameters for ethene and CO2 were determined via a van 't Hoff plot, where the entropy S was −11.982 J mol−1 K−1 <mfenced open="(" close=")">Δ<msubsup>SEthene0</msubsup></mfenced><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="56pt" height="22pt" class="svg-formula" dspmath="mathimg" md5hash="fc00baa5887d486a0db2d182899aca28"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="jsss-12-215-2023-ie00001.svg" width="56pt" height="22pt" src="jsss-12-215-2023-ie00001.png"/></svg:svg> and 1.351 J mol−1 K−1 <mfenced close=")" open="(">Δ<msubsup>SCarbon<mspace width="0.25em" linebreak="nobreak"/>dioxide0</msubsup></mfenced><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="84pt" height="22pt" class="svg-formula" dspmath="mathimg" md5hash="3d27dc819a29fda8555589e71bc3fd93"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="jsss-12-215-2023-ie00002.svg" width="84pt" height="22pt" src="jsss-12-215-2023-ie00002.png"/></svg:svg>, and the enthalpy H was −20.622 kJ mol−1 <mfenced close=")" open="(">Δ<msubsup>HEthene0</msubsup></mfenced><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="56pt" height="22pt" class="svg-formula" dspmath="mathimg" md5hash="7804adc56a831544bc982498ca3bd9d2"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="jsss-12-215-2023-ie00003.svg" width="56pt" height="22pt" src="jsss-12-215-2023-ie00003.png"/></svg:svg> and −14.792 kJ mol−1 <mfenced open="(" close=")">Δ<msubsup>HCarbon<mspace width="0.25em" linebreak="nobreak"/>dioxide0</msubsup></mfenced><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="85pt" height="22pt" class="svg-formula" dspmath="mathimg" md5hash="83cf6722d8d320131d6be54b342037da"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="jsss-12-215-2023-ie00004.svg" width="85pt" height="22pt" src="jsss-12-215-2023-ie00004.png"/></svg:svg>, respectively. Ethene (100 ppm) measurements revealed a system-specific correction term of 0.652 min. Further measurements of ethene and interfering gases revealed a mean retention time for ethene of 3.093 min; the mean predicted retention time is 3.099 min. The demonstrator was able to identify the test gas, ethene, as a function of the reference gas, CO2, in a first approach, without a column heating system and in a gas mixture by applying a temperature compensation algorithm and a system-specific holdup time correction term.